The Inauguration of Asian Pacific Journal of Environment and Cancer - yari, saeed; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2018)
On behalf of the Asian Pacific Organization for Cancer Prevention (APOCP) and its subsidiary (the West Asia Organization for Cancer Prevention- WAOCP), it is a great honor to present the inaugural issue of Asian Pacific Journal of Envirinment and Cancer (APJEC). APJEC is separated from the Asian Pacific Journal of Cancer Prevention and is determined to become a leading journal for scientists and researcher of the world. APJEC inherited its activity from the 19-year body of the successful publication of the Asian Pacific Journal of Cancer Prevention (APJCP) and considers itself to be the APJCP sister publications.